2021
DOI: 10.1177/0284185121989515
|View full text |Cite
|
Sign up to set email alerts
|

Utility of intraoperative magnetic resonance imaging for giant cell tumor of bone after denosumab treatment: a pilot study

Abstract: Background Giant cell tumor of bone (GCTB) is an intermediate but locally aggressive neoplasm. Current treatment of high-risk GCTB involves administration of denosumab, which inhibits bone destruction and promotes osteosclerosis. However, denosumab monotherapy is not a curative treatment for GCTB and surgical treatment remains required. Denosumab treatment complicates surgery, and the recurrence rate of GCTB is high (20%–30%). Purpose To examine the utility of intraoperative magnetic resonance imaging (iMRI) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In difficult-to-treat GCTBs conservative approaches have been conceptualized on the basis of breaking the vicious cycle established at the TME level in GCTB [5] , [12] . BPs like ZA are, besides their osteoclast inhibitory effects, believed to impair tumour growth by targeting both cellular components, MNGCs, and mutated H3F3A G34W + cells [18] , [19] , [20] , [21] , [22] , [23] , while RANKL inhibitors suppress only the osteoclastogenesis with limited direct effects on tumour cells [3] , [22] , [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In difficult-to-treat GCTBs conservative approaches have been conceptualized on the basis of breaking the vicious cycle established at the TME level in GCTB [5] , [12] . BPs like ZA are, besides their osteoclast inhibitory effects, believed to impair tumour growth by targeting both cellular components, MNGCs, and mutated H3F3A G34W + cells [18] , [19] , [20] , [21] , [22] , [23] , while RANKL inhibitors suppress only the osteoclastogenesis with limited direct effects on tumour cells [3] , [22] , [24] .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, iMRI has been utilized by other departments in their surgeries, such as bone tumors in orthopedics and liver cancer in gastrointestinal surgery. 36 ) It is also expected that iMRI will be more widely used in other fields.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Furuta et al [ 105 ] recently investigated the utility of intraoperative MRI for detection of residual tumors during surgical curettage in five patients with GCTB who received denosumab. The study demonstrated that iMRI was able to identify in all five cases suspected residual tumor tissue, confirmed by histopathology after additional curettage (detection rate was 100%), suggesting iMRI may represent a useful tool to promptly identify residual tumors and consequently prevent local recurrence.…”
Section: Imaging Contribution In Gctb Managementmentioning
confidence: 99%